2019
DOI: 10.5194/acp-19-835-2019
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of an intense wildfire smoke episode on surface radiation, energy and carbon fluxes in southwestern British Columbia, Canada

Abstract: Abstract. A short, but severe, wildfire smoke episode in July 2015, with an aerosol optical depth (AOD) approaching 9, is shown to strongly impact radiation budgets across four distinct land-use types (forest, field, urban and wetland). At three of the sites, impacts on the energy balance are also apparent, while the event also appears to elicit an ecosystem response with respect to carbon fluxes at the wetland and a forested site. Greatest impacts on radiation and energy budgets were observed at the forested … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…However, due to the smoke plumes persistent over the region during 7, 8, 10, and 11 September, solar power production was reduced compared to typical conditions by approximately 10%-30% during peak production hours (here considered 19-23 UTC or 12-16 Pacific Daylight Time (PDT)). Our findings agree well with those from previous studies focused on wildfire smoke impacts on solar reduction [22,36], including during the 2020 season in the Western U.S. [20,61]. In contrast, 9 September and the 12-16 September period featured solar production much closer to what is expected under typical conditions (less than 7% reduction) because the smoke plumes were transported out of the region.…”
Section: California Energy Market Operationssupporting
confidence: 91%
“…However, due to the smoke plumes persistent over the region during 7, 8, 10, and 11 September, solar power production was reduced compared to typical conditions by approximately 10%-30% during peak production hours (here considered 19-23 UTC or 12-16 Pacific Daylight Time (PDT)). Our findings agree well with those from previous studies focused on wildfire smoke impacts on solar reduction [22,36], including during the 2020 season in the Western U.S. [20,61]. In contrast, 9 September and the 12-16 September period featured solar production much closer to what is expected under typical conditions (less than 7% reduction) because the smoke plumes were transported out of the region.…”
Section: California Energy Market Operationssupporting
confidence: 91%
“…d Sum of chemically identified and unidentified species, from online updates to Akagi et al (2011). involving transport times and reaction rates of the species concerned. Because of their large spatial and temporal coverage, such measurements are quite valuable, and I have therefore included some of them in this assessment, as long as they were either dealing with long-lived species or used appropriate correction methods (i.e., chemistry-transport model calculations to correct for atmospheric transformations) (Rinsland et al, 2007;Mebust et al, 2011;Tereszchuk et al, 2011Tereszchuk et al, , 2013Schreier et al, 2015;Viatte et al, 2015;Lutsch et al, 2016;Adams et al, 2019). They can be compared with in situ measurement results by referring to the original data in the Supplement spreadsheet.…”
Section: Data Selectionmentioning
confidence: 99%
“…A short‐lived smoke event over southwestern British Columbia resulted in changes to the surface energy budget and some evidence of productivity enhancements in a bog ecosystem. At the same time, productivity decreased in a nearby coastal forest, although smoke density varied between the two sites (McKendry et al, ). Finally, an observational study in the Amazon rainforest found that under moderate, but not intense aerosol optical depths, diffuse fraction enhanced productivity (Yamasoe et al, ).…”
Section: Introductionmentioning
confidence: 99%